The Association of Weekly pre-Hemodialysis Systolic Blood Pressure and Following Week Mortality - Dugan Maddux; Len A. Usvyat; Danqing Xu; Yuedong Wang; Peter Kotanko; Frank M. van der Sande; Jeroen P. Kooman; Franklin W. Maddux (Karger Publishers, 2018)
Background/Aims: Few studies examine the impact of systolic blood pressure (SBP) on mortality in the incident hemodialysis (HD) period, and throughout the first HD year. This large retrospective observational study analyzes the impact of "current" and cumulative low preSBP <110 mmHg (L), and variations in preSBP on short-term (1 week) mortality over the first HD year. Methods: Weekly mean preSBP for HD weeks 1 to 51 was categorized into L or high preSBP>=110 mmHg (H) for each patient. A generalized linear model (GLM) was used to compute the probability of death in the following week. The model includes age, gender, race and three preSBP-related parameters: (a) percent of prior weeks with L preSBP; (b) percent of prior weeks with switching between L to H; (c) "current" week's preSBP as a binary variable. Separate models were constructed that include demographics and BP-related parameters (a), (b), and (c) separately. Results: In a model combining (a), (b), and (c) above, "current" week L preSBP is associated with increased odds ratio for following week mortality throughout the first HD year. The percent of prior week's L and more switching between L and H are less significantly associated with short-term mortality. In models including (a), (b), and (c) separately, "current" L preSBP is associated with higher mortality. Conclusion: This study confirms an association of L preSBP with increased short-term mortality which is maintained over the first HD year. Percent of L preSBP in prior weeks, switching between L and H, and "current" week L are all associated with short-term mortality risk, but "current" week L preSBP is most significant.